We Found Speaking More Joyful after Experiencing Dubbing Video Activity (A Case Study among Working Students) - Rahmawati, Sari (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2025)
This study aimed to investigate the effect of dubbing video activity on students’ speaking skill and students’ perceptions on it. This study was a mixed-method study by involving 19 working students of STMIK Jayanusa. Speaking pretest and posttest were applied to find out the effect of dubbing video activity on students’ speaking skill and they were analyzed by using SPSS. In addition, interview was conducted to get the data about students’ perceptions on dubbing video activity and they were analyzed by using NVivo. It turned out dubbing video activity affected students’ speaking skill proven by p = 0.03 (it was smaller than 0.05). Besides, the posttest mean scores were higher than the pretest mean scores (71.43 versus 69.22). The interviewed revealed that the students viewed this activity as an effective activity to improve their speaking skill. These findings showed that dubbing video can be an alternative activity in teaching especially.